PTU-113 How commonly is pancreatic cancer diagnosed following an endoscopic ultrasound that did not diagnose cancer?. (June 2019) - King, Dominic; Dosanjh, Amandeep; Patel, Prashant; Leeds, John; Nayar, Manu; Oppong, Kofi; Trudgill, Nigel
Abstract : Endoscopic Ultrasound (EUS) with tissue sampling has an established role in the diagnosis of pancreaticobiliary (PB) disease. Malignancy occurring following colonoscopy or gastroscopy that does not diagnose cancer is a recognised phenomenon and has been extensively investigated. There is little data on pancreatic cancer (PC) occurring following an EUS without evidence of cancer. We have studied the frequency, time course and potential risk factors for post EUS PC. Methods: PB EUS in England between Jan 2007 – Dec 2016 were identified in Hospital Episodes Statistics. Subjects with a diagnosis of PC made between 6 and 18 months after index PB-EUS were cases of post EUS PC. A logistic regression model examined risk factors for post EUS PC. Results: 79, 490 PB EUS procedures were performed in 69, 120 subjects, with 8, 859 diagnosed with PC within 6 months of index EUS. 563 (0.9%) subjects had post EUS PC (71% 6 to 12 months and 29% 12 to 18 months post EUS): median age was 70 (IQR 61–71) years and 57% were male. The following factors were associated with post EUS PC: chronic pancreatitis (odds ratio 3.11(95%CI 2.24–4.31), p<0.001); Charlson co-morbidity score >5 (1.44 (1.04–1.98), p=0.028); and increasing age (1.01(1.00–1.02), p=0.005) Ethnicity, gender and EUS volume were not associated with post EUS PC (table 1 ). Post EUS PC rates varied in individual providers from: 1.0% in providers undertaking 8 to 111 PB EUS over the study period to 1.1% in providers undertaking 112 to 782 PB EUS and 0.7% in providers undertaking >782 PB EUS. Conclusions: 0.9% of subjects undergoing a PB EUS that did not diagnose PC were diagnosed with PC between 6 and 18 months later. Post EUS PC was associated with chronic pancreatitis, co-morbidity and increasing age.